2017
DOI: 10.3390/en10091249
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and Optimization of the Melting Process of Phase Change Material inside Horizontal Annulus

Abstract: Latent heat storage (LHS) technologies adopting phase change materials (PCMs) are increasingly being used to bridge the spatiotemporal mismatch between energy production and demand, especially in industries like solar power, where strong cyclic fluctuations exist. The shell-and-tube configuration is among the most prevalent ones in LHS and thus draws special attention from researchers. This paper presents numerical investigations on the melting of PCM, a paraffin blend RT27, inside a horizontal annulus. The vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, the solidification time was longer in non-concentric DTHX, and consequently, the complete melting-solidification cycle was the shortest in concentric DTHX. However, Li et al [84] in their research took into account the volume expansion of the PCM during melting and consequently an air region at the top of the HX when the PCM was in the solid state. The results showed that lowering the inner tube did not influence the melting time of the PCM when the air region was taken into account.…”
Section: Double-tube Heat Exchangersmentioning
confidence: 99%
“…However, the solidification time was longer in non-concentric DTHX, and consequently, the complete melting-solidification cycle was the shortest in concentric DTHX. However, Li et al [84] in their research took into account the volume expansion of the PCM during melting and consequently an air region at the top of the HX when the PCM was in the solid state. The results showed that lowering the inner tube did not influence the melting time of the PCM when the air region was taken into account.…”
Section: Double-tube Heat Exchangersmentioning
confidence: 99%
“…They considered three configurations and found significant improvement in PCM thermal performance for the case of the proposed webbed tube heat exchanger as compared with shell‐and‐tube heat exchanger, multitube heat exchanger, and triplex tube heat exchanger. Li et al 16 studied numerical simulation and optimization of the melting process of PCM inside the horizontal annulus. They considered the eccentricity, diameter of the inner tube, subcooling degree of the PCM, and heating‐surface temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Delgado-Diaz et al [14] studied how to compare compactness and heat transfer performance for latent heat energy storage (LHES) modules with different designs. Li et al [15] observed the melting of phase change material inside a horizontal annular space using numerically simulation as well as optimizing.…”
Section: Introductionmentioning
confidence: 99%